Standardization and specification of balbas pusa Orthosiphon aristatus (Blume) Miguel (Family Labiatae) - Delos Reyes, Ma. Lourdes
A powdered drug of Orthosiphon aristatus (Blume) Miquel Family Labiatae was utilized for various testing procedures in order to come up with a set of standards and specifications for its crude drug. The tests performed were the following; foreign organic matter, water soluble extractive, dilute alcohol soluble extractive, moisture content, total ash and acid insoluble residue. Results showed a definite quantity of constituents contained in the crude drug. In addition, there is also a considerable content of inorganic matter which is approximated to be due to presence of adulterants.